Centrality dependence of the charged-particle multiplicity density at midrapidity in Pb-Pb collisions at √sNN=5.02 TeV - Adam, Jaroslav; Angelov, Venelin; Busch, Oliver; Danisch, Meike; Deisting, Alexander; Fleck, Martin; Glässel, Peter; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; Oyama, Ken; et al. (Physical review letters, 2016)
The pseudorapidity density of charged particles, dNch/dη, at midrapidity in Pb-Pb collisions has been measured at a center-of-mass energy per nucleon pair of √sNN=5.02 TeV. For the 5% most central collisions, we measure a value of 1943±54. The rise in dNch/dη as a function of √sNN is steeper than that observed in proton-proton collisions and follows the trend established by measurements at lower energy. The increase of dNch/dη as a function of the average number of participant nucleons, ⟨Npart⟩, calculated in a Glauber model, is compared with the previous measurement at √sNN=2.76 TeV. A constant factor of about 1.2 describes the increase in dNch/dη from √sNN=2.76 to 5.02 TeV for all centrality classes, within the measured range of 0%-80% centrality. The results are also compared to models based on different mechanisms for particle production in nuclear collisions.